THE EFFECT OF WORK ENVIRONMENT AND WORKLOAD ON EMPLOYEE PERFORMANCE IN PT. SOCFIN INDONESIA MEDAN - Marliana Harahap; Rini Astuti; Irwan Syari Tanjung (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2023)
The purpose of this study was to determine and analyze the effect of the work environment and workload on the performance of employees of PT. Socfin Indonesia Medan. The population in this study were employees of PT. Socfin Indonesia Medan.This research method uses a quantitative approach and uses associative reseach with questionnaire data collection techniques. with a sample of 126 people with a saturated sample. The data analysis technique in this study uses classical assumptions, multiple linear regression, F test and coefficient of determination. The results of this study can be concluded that together the work environment and workload have a significant effect on employee performance. This study resulted in a calculation that the work environment and workload had a significant effect on the performance of PT. Socfin Indonesia Medan. These results can be seen from the Fcount test of 58.139 from a significant level of 0.000 which is smaller = 0.05 and also the work environment and workload have a significant effect on employee performance as indicated by the R-square obtained by 0.486 (48.6%) , shows that 48.6% of employee performance variables can be explained by the work environment and workload variables, or practically it can be said that the contribution of the work environment and workload to employee performance is 48.6%, the remaining 51.4% is influenced by other variables. not researched.